Biología molecular del virus del rayado fino del maíz - León, Pedro; Gaméz, Rodrigo (Revista de Biología Tropical, 1986)
A condensed report of research on the molecular biology of Maize Rayado Fino Virus is offered, along with a tentative model for the capsid structure that fits the biochemical analysis of this virus. Given the existence of two capsid proteins present in a 7: 1 mass ratio it is suggested that in MRFV the major protein forms the closed icosahedral shell while the minor protein component is located externally.